Communities of Lifelong Learning [2]: Social Dialogue: Exchanges Shaping Learning Experiences - James E. Thornton; Shauna Butterwick; Thomas Sork (Adult Education Research Conference, 2010)
Social Dialogues discussed in this paper are the learning exchanges that develop in structured adult learning activities and essential communities of lifelong learning. Social dialogues, Social Justice and Social Territories and Borders (Session 1) are topics essential to the development of communities of lifelong learning. They provide the scaffolding critical to the professional and policy discourses shaping lifelong learning and educational opportunities over the adult life course in diverse social communities of practice.